2022
DOI: 10.1182/blood.2021014391
|View full text |Cite
|
Sign up to set email alerts
|

Systems medicine dissection of chr1q-amp reveals a novel PBX1-FOXM1 axis for targeted therapy in multiple myeloma

Abstract: Understanding the biological and clinical impact of copy number aberrations (CNA) for the development of precision therapies in cancer remains an unmet challenge. Genetic amplification of chromosome 1q (chr1q-amp) is a major CNA conferring adverse prognosis in several types of cancer, including in the blood cancer multiple myeloma (MM). Although several genes across chr1q portend high-risk MM disease, the underpinning molecular aetiology remains elusive. Here, with reference to the 3D chromatin structure, we i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 54 publications
1
24
0
Order By: Relevance
“…Among TFs, FOXM1 had highest enrichment score associated with sensitivity to a number of drugs of different classes: DOX, the mTOR inhibitor INK128, PANO, pomalidomide (POM), lenalidomide (LEN) and the PLK1 inhibitor volasertib (VOLA). These results are consistent with FOXM1 being an important regulator of drug resistance in MM 47 . Further, as an indication of the speci city of this unsupervised hypothesis-generating approach, we compared VOLA and BI2536: both are inhibitors of PLK1, a key regulator of cell cycle that phosphorylates FOXM1 that, in turn, regulates PLK1 expression 48,49 .…”
Section: Resultssupporting
confidence: 90%
“…Among TFs, FOXM1 had highest enrichment score associated with sensitivity to a number of drugs of different classes: DOX, the mTOR inhibitor INK128, PANO, pomalidomide (POM), lenalidomide (LEN) and the PLK1 inhibitor volasertib (VOLA). These results are consistent with FOXM1 being an important regulator of drug resistance in MM 47 . Further, as an indication of the speci city of this unsupervised hypothesis-generating approach, we compared VOLA and BI2536: both are inhibitors of PLK1, a key regulator of cell cycle that phosphorylates FOXM1 that, in turn, regulates PLK1 expression 48,49 .…”
Section: Resultssupporting
confidence: 90%
“…The simultaneous enhanced function of the expressed genes of the 1q21 amplicon may affect the resistance of different drugs. Recent studies have indicated that MM cells with 1q21 + seem to be more sensitive to inhibitory agents of MCL1 [ 74 ] and the PBX1-FOXM1 axis [ 75 ] compared with those lacking 1q21 + .…”
Section: Gain/amplification Of Chromosome Arm 1q21 (1q21 +)mentioning
confidence: 99%
“…Marchesini et al [ 8 ] found seventy-eight 1q21 genes either amplified or overexpressed by integrating 246 matched MM samples. Also, 103 candidate genes, located in chromosome 1q, were identified as prominent drivers of chr1q-amp multiple myeloma [ 13 ]. As a result, twenty-eight genes were both detected, including MCL1, ILF2, ADAR, CKS1B, and SETDB1 (supplemental Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…SETDB1 is mapped to human chromosome 1q21.3, one of seventy-eight amplified or overexpressed 1q21 genes by integrating GISTIC2 and expression data from 246 matched MM samples [ 8 ]. Also, systems medicine dissection of chr1q-amp identified 103 candidate genes, including SETDB1, as adverse prognostic biomarkers combined genomic, epigenomic, and transcriptomic data with genetic variables in MM [ 13 ]. Besides, the relationship between SETDB1 expression and its prognostic values in multiple myeloma has not been studied.…”
Section: Introductionmentioning
confidence: 99%